(untitled) (MAUSAM, 1978)
Seasonal and monthly global patterns of outgoing longwave radiation, albedo, absorbed solar radiation, and net radiation have been derived from scanning radiometer bservations aboard the NOAA polar orbiting satellites since June 1974. These patterns, along with patterns of interannual differences, in seasonal and monthly heating, are examined for the two summers of 1975-76 over the eastern hemisphere in relation to the variations in the summer monsoon and the major circulation features. During portions of the summer of 1975 the monsoon was more active than in 1976, as evidenced by increased albedo and decreased longwave radiation over large sections of India, the Indian Ocean, southeast Asia, and the western Pacific. The role of clouds, snow cover, and other surface characteristics in modulating the radiation balance and circulation is discussed. The pre-monsoon radiative heating in spring is examined with respect to monsoon onset and intensity in the two years.